Hemitransdomal versus Dome-Binding Suture - Casanueva, Fernando; Gerecci, Deniz; Cardemil, Felipe (Facial Plastic Surgery, 2018)
The dome-binding suture (DBS) and hemitransdomal suture (HTS) are suture techniques used to narrow and define the nasal tip. The DBS can create a pinched, unnatural appearance, while the HTS puts the lateral crus in a more favorable orientation. This allows a natural contour between the nasal tip and alar lobule while maintaining alar margin support. Objective measurement of the rotational axis of the lateral crus between the DBS and the HTS has not been reported in the literature. To determine whether the DBS or HTS technique results in a more favorable rotational axis of the lateral crus as measured by the alar surface septal angle (ASSA). Open rhinoplasty with cephalic trim and placement of a DBS or HTS was performed in 6 cadaveric heads, for a total of 12 lower lateral cartilages at the VirtuOHSU Simulation and Surgical Training Center at Oregon Health and Science University (OHSU). ASSA measurements were taken at baseline and after placement of either a DBS or HTS. A total of 36 ASSA measurements were obtained. The median baseline ASSA prior to suture placement was 142 degrees (interquartile range [IQR]: 131.5–145 degrees), following DBS placement was 141 degrees (IQR: 33–150.5 degrees), and following HTS placement was 112 degrees (IQR: 108–117 degrees). There was no statistically significant difference of ASSA measurements between baseline and DBS placement (p = 0.24), but there was a statistically significant difference between baseline and HTS (p < 0.0001) and between DBS and HTS (p < 0.0001). The HTS technique creates a more favorable rotational axis of the lateral crus as compared with the DBS, as measured by the ASSA. This study provides objective data to support the use of the HTS for nasal tip contouring.
Keywords: rhinoplasty; nasal tip contour; suture techniques